Loving-kindness meditation (LKM) modulates brain-heart connection: An EEG case study - Wong, GoonFui; Sun, Rui; Adler, Jordana; Yeung, Kwok Wah; Yu, Song; Gao, Junling (Frontiers in Human Neuroscience, 2022)
Loving-Kindness Meditation (LKM) is an efficient mental practice with a long history that has recently attracted interest in the fields of neuroscience, medicine and education. However, the neural characters and underlying mechanisms have not yet been fully illustrated, which has hindered its practical usefulness. This study aimed to investigate LKM from varied aspects and interactions between the brain, the heart, and psychological measurements. A Buddhist monk practitioner was recruited to complete one 10-min LKM practice, in between two 10-min resting tasks (pre- and post-resting) per experimental run. Two sets of single-channel wearable EEG devices were used to collect EEG data (placed at Fz and Pz) and heart rate simultaneously. A self-report evaluation was conducted to repeatedly record the comprehensive performance of mind and body in each session. EEG data were preprossessed and analyzed by EEGlab. Further statistics were made by SPSS. Spectrum analysis showed a significant increase of theta power (Fz: t = −3.356; p = 0.002; Pz: t = −5.199; p < 0.001) and decrease of heart rate between pre- and post-resting tasks (t = 4.092, p < 0.001). The analysis showed a negative correlation between theta power and heart rate (Fz: r = −0.681, p < 0.001; Pz: r = −0.384, p = 0.008), and a positive correlation between theta power and the self-designed report score (Fz: r = 0.601, p < 0.001). These findings suggest that LKM is accompanied by significant neurophysiological changes, mainly an increase in slower frequencies, such as theta, and a decrease in heart rate. More importantly, subjective psychological assessments were also correlated with objective neurophysiological measurements in a long-term meditator participant. During LKM meditation, this connection was stronger. The results of this case report have promising implications for LKM practice in daily life.